Taking an alternate route: redesigning sales management control systems for new product selling - Kohsuke Matsuoka; Hiromune Ishii; Ying Zhu; Asumi Kawaguchi (Cogent Business & Management, 2024)
Salespeople play a critical role in new product selling. Owing to the time lag between sales efforts and accounting outcomes, salespeople under budget pressure created by outcome-based control systems may engage in myopic revenue management by prioritizing the selling of existing products. While increasing sales efforts through activity-based control systems has been considered effective in alleviating this problem, opponents argue that it results in micromanagement and undermines new product selling. Recognizing these issues, this study conducted an empirical analysis using repeatedly measured objective data from an electronic component trading company in Japan to examine the feasibility of a sales management control system redesign. The analysis revealed that sales effort quantity had a negative effect on sales quotas but was positively related to revenue mileposts, such as project generation and closing. Furthermore, the effects of sales effort quantity on revenue mileposts weaken as sales effort quality increases. The results imply that outcome-based control systems are more effective for smart workers with high sales effort quality and activity-based control systems are more effective for hard workers with low sales effort quality.
Keywords: 650; Sales management control systems; new product selling; myopic revenue management; revenue milepost; sales effort quantity; sales effort quality